Consumer evaluation of food quality and the role of environmental cues: A comprehensive cross-country study - Dacinia Crina Petrescu; Iris Vermeir; Philippe Burny; Ruxandra Malina Petrescu-Mag (European Research on Management and Business Economics (ERMBE), 2022)
Widely explored in literature, yet it is unclear which food quality cues consumers find most relevant. The increasing consumers' concern for sustainability aspects in their food buying decisions warrants special attention to environmental-social aspects as food quality indicators. Consequently, this study explores consumer evaluation of food quality and highlights the role of environmental-social cues in food quality evaluation. A cross-national perspective was adopted, using a sample of 761 consumers from Belgium and Romania. Exploratory factor analysis reveals six factors that contained food quality cues perceived as similar by consumers. The first factor, named "Environmental-Social", comprises cues related to environmental protection and social equity. Regression analyses indicate a set of variables that can predict the perceived relevance of environmental-social cues in food quality evaluation. The present study contributes to understanding of consumer food quality evaluation by extending the analysis to a large number (59) of food quality cues. From a practical stance, the study can guide managers' efforts to enhance environmentally sustainable behavior based on the relevance of environmental-social cues in consumers' food quality evaluation.
Keywords: M31; L15; 650; Cue similarity; Food; Questionnaire; Social; Sustainability